Second Year Winner: Ethiopia and Policy: SOSC 2800, Development in Comparative and Historical Perspective. CD: Merouann Mekouar. - Janmohamed, Samir (Noteworthy: The LA&PS Writing Prizes, 2016)
The paper is a response to an assignment that asks students to present an analytical description of the current economic, political and social conditions in a selected developing country, and then the present a series of policy prescriptions that address the challenges posed by those conditions. Mr. Janmohamed’s paper offers a highly effective and detailed exposition of current conditions in Ethiopia and presents well-argued recommendations for changes to current policies. The paper is well-researched and offers telling comparisons with the successes and failures of policies in other, roughly analogous developing countries. The readers were particularly impressed by the paper’s discussion of the limitations of Ethiopia’s currently successful emphasis on industrial development at the expense of agriculture. Mr. Janmohamed’s self-invocation on this point is a particularly telling rhetorical strategy.